Long-term Dose Stability of OnabotulinumtoxinA Injection for Adductor Spasmodic Dysphonia: A 19-Year Single Institution Experience - Paddle, Paul; Husain, Inna; Moniz, Christine; Turner, Scott; Franco, Ramon Arturo (Frontiers in Surgery, 2017)
Objectives: Adductor Spasmodic Dysphonia (AdSD) is a focal dystonia predominantly involving the laryngeal adductor muscles. AdSD is reported to be a largely non-progressive neurological disorder, though fluctuations in symptom severity do occur. Repeated laryngeal onabotulinumtoxinA (BTX-A) injections are the primary management for adductor spasmodic dysphonia (AdSD). A number of studies have demonstrated long-term dose stability as evidence of this long-term disease stability. Methods: A retrospective review was performed on all patients undergoing BTX-A injections for AdSD from April 1994 to September 2013 by a single laryngologist at a tertiary referral laryngology center. Patient demographics, injection doses, use of diazepam and/or lidocaine, and self-reported vocal function were recorded. Multiple linear regression analyses were performed. Results: 83 patients underwent a total of 1,168 injections over 19 years. The mean starting dose was 2.35 MU (0.79 SD). The mean long-term dose was 2.36 MU (0.79 SD). After adjusting for confounders, the change in the relative dose of BTX-A, with every year elapsed since initial dose was 0.13% (95% Confidence interval -0.31% to 0.57%), p=0.568 Conclusions: BTX-A dose is stable over time in our large cohort of patients treated with bilateral thyro-arytenoid injections for Adductor Spasmodic Dysphonia.